Public lecture of judge Atanaska Disheva – member of the Supreme Judicial Council – before law students on the topic: “The role of the prosecutor in the administrative proceedings - Nikolova, Raina (Law Journal of New Bulgarian University, 2021)
The public lecture is dedicated to the issue of the prosecutor’s supervision on the activities of the administrative bodies within the principle of separation of powers and the principle of rule of law. It provides the opportunity to make more specific the scope of the prosecutor’s function on ensuring the legal order.